Предмет: Алгебра, автор: shitovandrey85

помогите срочнооооооооооооо​

Приложения:

Ответы

Автор ответа: hote
0

Чтобы выполнить задание нужно просто выучить формулы

\displaystyle (a+b)^3=a^2+3a^2b+3ab^2+b^3\\\\(a-b)^3=a^3-3a^2b+3ab^2-b^3

тогда

\displaystyle (x+y)^3=x^3+3x^2y+3xy^2+y^3\\\\(b-y)^3=b^3-3b^2y+3by^2-y^3\\\\(t^2+4)^3=(t^2)^3+3(t^2)^2*4+3t^2*4^2+4^3=t^6+12t^4+48t^2+64\\\\(d-p)^3=d^3-3d^2p+3dp^2-p^3\\\\(g-2)^3=g^3-6g^2+12g-8\\\\(n-m)^3=n^3-3n^2m+3nm^2-m^3\\\\(4m+n)^3=64m^3+48m^2n+12mn^2+n^3\\\\(3+n)^3=27+27n+9n^2+n^3\\\\(2y+5r)^3=8y^3+60y^2r+150yr^2+125r^3\\\\(3y-2x)^3=27y^3-54y^2x+36yx^2-8x^3

Похожие вопросы